Agricultural productivity current scenario, constraints and future prospects in Pakistan - Aslam, Muhammad (ResearchersLinks Ltd, 2016)
This review paper intends to portray current scenario of agricultural productivity through yields and gaps of five major crops; wheat, cotton, rice, maize and sugarcane. The review discusses major constraints, identifies future prospects and makes policy recommendations for enhanced agricultural productivity in Pakistan. The review revealed that in Pakistan, on average current yield of wheat, cotton, rice, maize and sugarcane is 2.26, 1.87, 2.88, 1.77 and 48.06 tons per hectare, respectively against 6.80, 4.30, 5.20, 9.20 and 300 tons per hectare potential yield of wheat, cotton, rice, maize and sugarcane, respectively, obtained through research. This reflects a yield gap of 67, 57, 45, 81 and 84 % between average and potential yield of wheat, cotton, rice, maize and sugarcane, respectively. The review also informed that current Pakistan’s average yield of wheat, cotton, rice, maize and sugarcane is 70, 53, 61, 82 and 60%, respectively lower than the average yields obtained internationally. Major constraints include agronomic, irrigation management, environmental, technological, institutional and socio-economic constraints. Future prospects include upscaling of modern technology, enhanced seed production, improved inputs availability and use, improved irrigation, improved agriculture-education-training-research- extension-nexus, reclamation of salinized lands, improved agricultural credit and support price policies. Recommendations include improving agricultural research and extension systems, accelerating diffusion and adoption of latest agriculture technologies and inputs, enhancing good quality seed production, improving irrigation water management and improving reclamation and drainage.